2014
DOI: 10.1007/s10278-014-9699-7
|View full text |Cite
|
Sign up to set email alerts
|

Creation and Implementation of Department-Wide Structured Reports: An Analysis of the Impact on Error Rate in Radiology Reports

Abstract: The purpose of this study was to evaluate and compare textual error rates and subtypes in radiology reports before and after implementation of department-wide structured reports. Randomly selected radiology reports that were generated following the implementation of department-wide structured reports were evaluated for textual errors by two radiologists. For each report, the text was compared to the corresponding audio file. Errors in each report were tabulated and classified. Error rates were compared to resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 10 publications
(23 reference statements)
3
29
0
2
Order By: Relevance
“…Structured radiology reporting promised to improve report quality as structures are described in a regular and predictable order and there is a decrease of missense-omission errors (words omitted from dictations which ultimately change the intended meaning) [11,9]. Indeed, a recent study has demonstrated that structured chest radiograph reports are more complete and effective than unstructured reports [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structured radiology reporting promised to improve report quality as structures are described in a regular and predictable order and there is a decrease of missense-omission errors (words omitted from dictations which ultimately change the intended meaning) [11,9]. Indeed, a recent study has demonstrated that structured chest radiograph reports are more complete and effective than unstructured reports [10].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study has demonstrated that structured chest radiograph reports are more complete and effective than unstructured reports [10]. Furthermore, fields for entry of specific data within a structured report have the potential to direct radiologists' search patterns and facilitate consistent reporting of findings that would not otherwise have elicited specific comment if the radiologist was using free-style dictation [8,11,12,13]. Radiologists tasked with creation of standardized reports for an organization may incorporate the latest thinking on value-adding imaging data and suggest items for incorporation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common dictation errors related to SR generated reports include, but are not limited to, wrong-word substitution, nonsensical phrases, and errors of omission [13][14][15][16]. Reports may also contain clinical errors that are not specific to the SR software.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to patient care, these reports are commonly components of educational, research, legal, and billing purposes. The use of structured reporting has been shown to improve image interpretation and surgical planning compared with nonstructured reports [20][21][22]. However, multiple studies indicate that radiology report guidelines and templates insufficiently address clear objectives and implementation issues [18,19,23].…”
Section: Improve Radiology Reports Implement Structured Reportsmentioning
confidence: 97%